Analisis Laju Perpindahan Panas Sistem Pendingin Air Tawar pada Engine Generator Listrik - Kaminton Tambunan; Zainal Fanani; Muji Prihajatno (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
Generator engine is a propulsion that generates power to run a power plant. Heat control on the engine generator with a fresh water cooling system serves to stability maintain of the temperature engine. The water cooling system to absorb heat from combustion process heat transfer analysis is carried out based on measurements and calculations to find out optimally the work of the generator engine. Experimental research methods are carried out by to many cooling water drums easly cooling water, and increasing volume of cooling water. Based on the results of experimental analysis and calculations that the standard cooling at 1500 rpm an average Qcooling = 79,979.23 Watt; and the percentage of heat absorption = 14.04%. Cooling with drum cooling at 1500 rpm an average Qcooling = 32,737.60 Watt; and the percentage of heat absorption = 41.44%. Cooling with drum cooling and add of cooling water volum at 1500 rpm average Qcooling = 27,350.40 Watt; and the percentage of heat absorption = 75.79%. The used of drum cooling and addition of cooling water volum will optimalized the cooling rate.